In Situ Fracture of Stents Implanted for Relief of Pulmonary Arterial Stenosis in Patients with Congenitally Malformed Hearts - McElhinney, Doff B. (Cardiol Young, 2008)
BACKGROUND: One of the most common uses of stents in patients with congenitally malformed hearts is treatment of pulmonary arterial stenosis. Although there are reports of fractured pulmonary arterial stents, little is known about the risk factors for, and implications of, such fractures. METHODS: We reviewed angiograms to identify fractures in stents previously inserted to relieve stenoses in pulmonary arteries from 1990 through 2001 in patients who also underwent follow-up catheterization at least 3 years after placement of the stent. We undertook matched cohort analysis, matching a ratio of 2 fractured to 1 unfractured stent. RESULTS: Overall, 166 stents meeting the criterions of our study had been placed in 120 patients. We identified fractures in 35 stents (21%) in 29 patients. All fractured stents were in the central pulmonary arteries, 24 (69%) in the central part of the right pulmonary artery, and all were complete axial fractures, or complex fractures along at least 2 planes. Stent-related factors associated with increased risk of fracture identified by multivariable logistic regression included placement in close apposition to the ascending aorta (p = 0.001), and a larger expanded diameter (p = 0.002). There was obstruction across 28 of 35 fractured stents, which was severe in 11. We re-stented 21 of the fractured stents, and recurrent fracture was later diagnosed in 3 of these. A fragment of the fractured stent embolized distally in 2 patients, without clinically important effects. CONCLUSIONS: In situ fracture of pulmonary arterial stents is relatively common, and in most cases is related to compression by the aorta. There is usually recurrent obstruction across the fractured stent, but fractured stents rarely embolize, and are not associated with other significant complications.